Emphasizing Digital Governance and Development Empowering Rural Transformation through Village Information Systems (SID): Evidence from Aceh Tamiang, Indonesia: English - Vaneysha, Vini; Lubis, Satia Negara; Taufiq, Muhammad (CV. ARGA FARMA, 2025)
This study investigates the role of the Village Information System (Sistem Informasi Desa/SID) in accelerating rural development by examining the influence of three critical supporting factors: human resources, infrastructure, and IT services. Focusing on Kota Kualasimpang Subdistrict in Aceh Tamiang, Indonesia, the research adopts a quantitative approach involving 99 respondents selected from five villages through accidental sampling. Data were collected via structured questionnaires and analyzed using descriptive statistics, validity and reliability testing, classical assumption diagnostics, and multiple linear regression. The findings reveal that all three factors—human resources, infrastructure, and IT services—significantly and positively impact the acceleration of rural development. Among these, IT services exhibit the most substantial influence, highlighting the strategic importance of technological readiness in local governance. The study underscores the vital role of digital infrastructure and capacity building in promoting effective and inclusive village-level development, particularly in autonomous regions such as Aceh. The results offer empirical insights for policymakers and practitioners aiming to optimize SID implementation as a transformative tool for sustainable rural advancement.